Management Strategy of Instagram @cbp.rupiah as A Literacy Media to Enhance Public Understanding of Rupiah Currency by Central Bank of Indonesia 2024-2025 - Fadhlan AlHafidz; Fajar Junaedi (Jogjakarta Communication Conference (JCC), 2025)
Social media has become a strategic tool for public education, including financial literacy. Bank Indonesia utilizes Instagram @cbp.rupiah to enhance the Indonesian public’s understanding of Rupiah. This study aims to analyze the management strategies of the account and provide recommendations to improve its impact. Using a qualitative descriptive method, this research collects data through interviews, documentation, and literature studies, which are then analyzed using the Miles and Huberman model. The research findings indicate that the management strategy of the @cbp.rupiah Instagram account includes interactive content planning, utilization of Instagram features, and the implementation of a communication style that aligns with digital trends and the characteristics of the target audience. This approach aims to increase user engagement, strengthen interactions with the public, and deliver educational messages about Rupiah in a more engaging, easily understandable, and digitally relevant manner. This study recommends collaboration with educational influencers, increasing interaction through participatory content, and optimizing data analytics. With the right strategies, social media can serve as an effective tool for enhancing financial literacy in society.